Managerial economics (Vikas, 2013)
Managerial economics deals with the science of applying economics to the business situations within an organization. The books begins with an overview of managerial economics, its definition meaning and importance-- It introduce the readers to the important terms and concept related to the subject. the book aims to help managers take appropriate business decisions by discussing the concepts theories and tools of economic analysis. The book follows a structured pattern where every chapter begins with learning objectives followed by an introduction to the topic. each chapter concludes with a summery of the key points, a list of key terms ans set of questions and exercises for effective recapitulation. The further reading section creates a research interest in students for further exploration of the topic covered